Profil Lulusan Program Studi PGSD Universitas PGRI Adi Buana Surabaya - Apri Irianto; Bahauddin Azmy; Susi Hermin Rusminati (Jurnal Studi Guru dan Pembelajaran, 2021)
This study aims to find out the jobs of alumni after they have studied at pgsd study program of PGRI Adi Buana University Surabaya. This research uses qualitative method using source triangulation. How to retrieve data on this thesis is to ask questions using google form and then distributed in alumni group. from the results of this study it can be known that 71% of students with a waiting time of less than 3 months, 7% of alumni are certified, 91% of people work in accordance with the field of education.